TAS WANITA BERHIASAN BUNGA KAMBOJA DENGAN TEKNIK KOIL DAN SIMPUL - ANGI MUSTIKA DEWI, Dra. Minarsih, M.Sn., Drs. Erwin A, M.Sn. (Universitas Negeri Padang, 2016)
Adolescent always using bag everywhere them going . To support appearance of woman which like to dress smartly and combine to befit bag colour with clothes colour. Making of this final masterpiece bag aim to create seven woman bag of ekslusif dress smartly flower of kamboja. Matting method technique of koil and node. Time in making of this final masterpiece from March until June 2016. The result of masterpiece : Loyalty Blue Kamboja, Violet Imajiantion Kamboja, Green Brave Red Kamboja, Black Violet Elegant Kamboja, Romantic Pink Kamboja, Brave Black Kamboja, Green Fresh Kamboja. Suggested to and pekriya of perajin to produce appropriate bag of appetite its user wearer age.Kata Kunci : Tas Wanita, Kamboja, Koil, Simpul